2020
DOI: 10.1002/cbdv.202000652
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Rosavin from Rhodiola rosea on Radiation‐Induced Intestinal Injury

Abstract: Bioactive constituents from Rhodiola rosea L. (RRL) exhibit multiple pharmacological effects on diverse diseases. However, whether they are suitable for the treatment of radiation-induced intestinal injury (RIII) remains unclear. This study aims to investigate their roles and mechanisms in the RIII rat model. The radioprotective effects of the four bioactive constituents of RRL (salidroside, herbacetin, rosavin and arbutin) were evaluated by the cell viability of irradiated IEC-6 cells. Intestinal tissues were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
(65 reference statements)
1
5
0
Order By: Relevance
“…The Rosavin therapy significantly reduced the levels of TNF-α and interleukin IL-1β; attenuated neutrophil infiltration; elevated the anti-inflammatory cytokine IL-10; moreover reduced the MDA levels; and increased the activities of the antioxidant enzymes SOD, CAT and GSH-Px. The Rosavin therapy markedly improved intestinal damage and increased the survival rate in the irradiated rats [45]. This study suggests that Rosavin can be an effective drug for the treatment of RIII.…”
Section: Digestive System Diseasessupporting
confidence: 51%
See 1 more Smart Citation
“…The Rosavin therapy significantly reduced the levels of TNF-α and interleukin IL-1β; attenuated neutrophil infiltration; elevated the anti-inflammatory cytokine IL-10; moreover reduced the MDA levels; and increased the activities of the antioxidant enzymes SOD, CAT and GSH-Px. The Rosavin therapy markedly improved intestinal damage and increased the survival rate in the irradiated rats [45]. This study suggests that Rosavin can be an effective drug for the treatment of RIII.…”
Section: Digestive System Diseasessupporting
confidence: 51%
“…A total of 25 µM Rosavin increased cell viability from approximately 60% to 90% after 10 Gy γ-rays irradiation [44]. After the irradiation of IEC-6 (rat small intestinal crypt epithelial cells), the proliferation activity of the cells was enhanced to different degrees after the intervention of Salidroside, Rosavin and Arbutin, among which 12.5 µM Rosavin had the most potent protective effect, increasing the cell viability to 85.56 ± 4.93% [45]. The above studies demonstrated the strong radiation resistance of Rosavin in cells.…”
Section: Antiradiation Effectmentioning
confidence: 99%
“…The pathogenesis of radiation-induced intestinal injury is multifactorial and mainly related to cell apoptosis in the crypt epithelium and inflammatory processes [ 5 , 32 ]. Apoptosis is one of the most important outcomes of irradiation-mediated intestinal damage.…”
Section: Discussionmentioning
confidence: 99%
“…However, this therapy can lead to various complications, including radiation-induced intestinal injury [ 1 3 ]. Intestinal injury, a common complication with an incidence rate of 50–70% [ 4 , 5 ], leads to weight loss, diarrhea, intestinal strictures/fistulas, and even severe enteric septicemia, all of which can seriously affect the patient's quality of life [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study has reported that arbutin has a protective effect on ethanol and aspirin-induced gastric ulcer animal models by regulating cytokine levels [ 1 ]. Recent studies have also shown that arbutin can increase the cell viability of intestinal epithelial cells [ 11 ]. It has been found that arbutin can act as a hydroxyl radical scavenging agent and inhibit the activation of p-JNK and p38 MAPK signaling proteins [ 12 ], and inhibition of p-JNK and p38 MAPK signaling can reduce the damage of DSS-induced UC in mice [ 9 ].…”
Section: Introductionmentioning
confidence: 99%